Cucurbit[8]uril-mediated supramolecular photoswitching for self-preservation of mesoporous silica nanoparticle delivery system1. Issue 65 (21st August 2015) - Ma, Ning; Wang, Wen-Jing; Chen, Si; Wang, Xiao-Shuang; Wang, Xiao-Qiang; Wang, Shi-Bo; Zhu, Jing-Yi; Cheng, Si-Xue; Zhang, Xian-Zheng
<x xml:space="preserve">Abstract</x> The self peptide was introduced into the drug loaded mesoporous silica nanoparticle surface through a supramolecular photoswitchable heteroternary complexation, leading to photosensitive drug release.